2016
DOI: 10.1039/c5np00110b
|View full text |Cite
|
Sign up to set email alerts
|

Discoveries, target identifications, and biological applications of natural products that inhibit splicing factor 3B subunit 1

Abstract: Covering: 1992 to 2015The natural products FR901464, pladienolide, and herboxidiene were discovered as activators of reporter gene systems. Unexpectedly, these compounds target neither transcription nor translation; rather, they target splicing factor 3B subunit 1 of the spliceosome, causing changes in splicing patterns. All of them showed anticancer activity in a low nanomolar range. Since their discovery, these molecules have been used in a variety of biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 81 publications
0
34
0
6
Order By: Relevance
“…A number of groups, including the Koide,[11] Webb,[12] Ghosh-Jurica,[13] Hoveyda,[14] Alvarez-Valcárcel,[15] and Nicolaou[17] groups, as well as Koehn and co-workers,[16] have explored the second and third families (Figure 4). In the first example, Webb used a Julia--Kocienski olefination strategy to complete the backbone of 4 ((Figure 4 a, blue), with the C(12)<C->C(13) epoxide being added in the last step.…”
Section: The Chemistry Of Splice Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of groups, including the Koide,[11] Webb,[12] Ghosh-Jurica,[13] Hoveyda,[14] Alvarez-Valcárcel,[15] and Nicolaou[17] groups, as well as Koehn and co-workers,[16] have explored the second and third families (Figure 4). In the first example, Webb used a Julia--Kocienski olefination strategy to complete the backbone of 4 ((Figure 4 a, blue), with the C(12)<C->C(13) epoxide being added in the last step.…”
Section: The Chemistry Of Splice Modulationmentioning
confidence: 99%
“…[12] Alternatively, the Koide group’s synthesis of 6 illustrated the use of olefin cross-metathesis to bring together both fragments ((Figure 4 b, blue). [11] The third approach was demonstrated by the Nicolaou group’s synthesis of 8 , which involved the use of a Suzuki coupling to unite the two olefins of the internal diene. [17]…”
Section: The Chemistry Of Splice Modulationmentioning
confidence: 99%
“…Der Zugang zu Spleißmodulatoren (SPLMs) hat sich von den frühen Stadien der Naturstoffisolierung [3][4][5] bis zum heutigen Stand der medizinalchemischen Optimierung und zuverlässigen Totalsynthese [6][7][8][9][10][11][12][13][14][15][16][17] weiterentwickelt. Aktuell haben die am besten charakterisierten SPLMs den gleichen Wirkmechanismus ("mode of action", MOA);sie sind gegen die Multiproteinkomponente SF3b innerhalb des kleinen nukleären Ribonukleoproteins (snRNP) U2 im Spliceosom gerichtet.…”
Section: Die Chemie Der Spleißmodulationunclassified
“…Bei unseren Untersuchungen zu 3 (Abbildung 3c) [7] wur- Eine Reihe von Arbeitsgruppen, darunter die von Koide, [11] Webb, [12] Ghosh-Jurica, [13] Hoveyda, [14] Alvarez-Valcµrcel [15] und Nicolaou [17] ebenso wie Koehn et al [16] zweite und dritte Strukturfamilie untersucht (Abbildung 4). Im ersten Beispiel schlug Webb eine Julia-Kocienski-Olefinierungsstrategie ein, um das Gerüst von Fragment 4 zu vervollständigen (Abbildung 4a,b lau), an dem das C(12)-C-(13)-Epoxid im letzten Schritt eingeführt wurde.…”
Section: Herausforderungen Und Lçsungen Bei Der Syntheseunclassified
“…In the search of the mechanism by which Pladienolide B or E-7107 promote the formation of a defective spliceosome, it was found that E7 blocks ATP-dependent remodeling of U2 snRNP that exposes the branch point-binding region. Under this scenario, U2 snRNP fails to bind tightly to the pre-mRNA without disrupting the U2 particle or its association with SF3b [49, 103]. …”
Section: Mechanistic Insightsmentioning
confidence: 99%